Evaluation of Direct and Nested PCR for the Detection of Hepatitis B Virus in Chronic Carriers and Asymptomatic Blood Donors - Al-Safi, Mushtaq Talib (American Journal of Biology and Natural Sciences, 2025)
Severity of HBV contamination is directly associated with immunological responses in the host, both those of an antibody and cellular nature, whereby immunological responses are a key public health burden. In this study, the properties of virus genetics responded to immunity and clinical stage in chronic HBV patients of Iraq compared to healthy HBsAg-positive patients. The researchers also wanted to demonstrate that immunological status was significantly associated with liver disease severity and duration of disease. Finally, sixty healthy participants and sixty others with chronic hepatitis B type B in Nasiriyah city between June 2014 and February 2016 were included in this study in liver and gastrointestinal disease centers at the University Hospital and Thalassemia Centre. The average age of chronic hepatitis B patients has persisted in rising and reached 64.5 years in February 2024–2025. The study found that the healthy HBsAg youngsters were, on average, 35.1 years old. Men were 13.6 times as likely as women and 12.2 times as likely as men with chronic conditions to have the condition. Gender inequality has consequences for population health. Nested PCR amplification method revealed that the genetic material present in the samples investigated (both sick and asymptomatic carriers) was DNA. Positivity of PCR was 30.0% in chronic disease patients and 46.7% in healthy carriers. Clear, clean, yes, separating out the two concurrent conversations. The identification of hepatitis B virus genetic material (HBV DNA) in Iraqi patients with chronic hepatitis B by nested polymerase chain reaction (nested PCR) shows greater sensitivity and informativeness. The latest recommendations issued in Iraq for diagnosing viral hepatitis include screening for viral load, coupled with nucleic acid testing and RT-PCR.